Preventing duplication of digital audio file in personal divice using Biologically-Inspired Audio Storing Management Process (BIASMP) - Hamzah, Hammuzamer Irwan; Low, Tan Jung; Abdul Mutalib, Ariffin (2013)
This paper presents biologically-inspired audio storing management process (BiASMP) to prevent duplication of digital audio filein personal storage.There are certain digital music application tools that detect duplication and provide cleaning function. However duplication still happen until the software is executed by user.This paper inspires the biologically human concept to create a process that capable to prevent duplication of digital audio files from the start of the file is inserted into the personal device.The elements to establish BiASMP are analyzed and studied.Comparative analysis between current tools and BiASMP is made and the results of exemplar simulations are shown to authenticate the developed process.